Ethics of sport and athletics : theory, issues, and application - Schneider, Robert C. (Philadelphia : Wolter Kluwer, 2009)
Learn the theories and mechanics of moral reasoning, ethical and unethical behavior in sport, and the development of moral education through sport.
Part I : Moral theory in sport and athletics -- Part II : Moral application in sport and athletics
Includes bibliographical references and index.
Keywords: SPORTS -- ASPECT MORALS